Genomic characterization of vancomycin-resistant Enterococcus faecium clonal complex 17 isolated from urine in tertiary hospitals in Northeastern Thailand - Chopjitt, Peechanika; Boueroy, Parichart; Jenjaroenpun, Piroon; Wongsurawat, Thidathip; Hatrongjit, Rujirat; Kerdsin, Anusak; Sunthamala, Nuchsupha (Frontiers in Microbiology, 2024)
Vancomycin-resistant Enterococci (VREs) have increasingly become a major nosocomial pathogen worldwide, earning high-priority category from the World Health Organization (WHO) due to their antibiotic resistance. Among VREs, vancomycin-resistant Enterococcus faecium (VREfm) is particularly concerning, frequently isolated and resistant to many antibiotics used in hospital-acquired infections. This study investigated VREfm isolates from rural tertiary hospitals in Northeastern Thailand based both antibiotic susceptibility testing and whole-genome sequencing. All isolates showed resistance to vancomycin, ampicillin, erythromycin, tetracycline, ciprofloxacin, norfloxacin, and rifampin. Nitrofurantoin and tigecycline resistance were also observed in nearly all isolates. Conversely, all isolates remained susceptible to chloramphenicol, daptomycin, and linezolid. Genomic characterization revealed that all VREfm isolates belonged to clonal complex 17 (CC17), primarily consisting of sequence type (ST) 80, followed by ST17, ST761, and ST117. Additionally, all isolates harbored numerous antimicrobial-resistant genes, including vanA, tet(L), tet(M), aac(6)-li, ant(6)-Ia, aph(3)-III, aac(6’)-aph(2”), aph(2")-la, ant(9)-la, erm(B), msr(C), erm(T), erm(A), fosB, dfrG, and cfr(B). Notably, all isolates contained virulence genes, for collagen adhesin (acm) and cell wall adhesin (efafm), while hylEfm (glycosyl hydrolase) was detected in VREfm ST80. This study provided important information for understanding the genomic features of VREfm isolated from urine.